Food-Grade Bioactive Ingredient Obtained from the Durvillaea Incurvata Brown Seaweed: Antibacterial Activity and Antioxidant Activity - Palacios-Pino, J; Verdugo, L (Elsevier B.V., 2022)
Natural antioxidants have been extracted and identified from different types of marine seaweeds for developing new food-grade functional ingredients and drugs. In this study, a food-grade bioactive ingredient (FGBI) containing functional bioactive carotenoids was obtained from Durvillaea incurvata (D. incurvata) brown edible seaweed, which was subjected to an alternative postharvest drying process (sunlight radiation protection) to preserve the fucoxanthin content. Moreover, FGBI was prepared from the part of the structure of seaweed where the fucoxanthin is mainly concentrated (external structure of the D. incurvata). The nutritional value of D. incurvata was evaluated and the major macronutrients contained in the brown seaweed were the dietary fiber (56.9 g/100 g, dry weight), ash (20.9 g/100 g, dry weight), and protein (8.30 g/100 g, dry weight). In addition, its heavy metal content is in the safe range to be consumed. Regarding the antibacterial activity of the FGBI-extract (dried ethanolic extract from FGBI), the lowest minimum inhibitory concentration (MIC) values were evidenced for Staphylococcus aureus (0.06 mg/mL), Listeria monocytogenes (0.1 mg/mL), and Enterococcus feacalis (0.5 mg/mL). The DPPH radical scavenging activity was dependent on the FGBI-extract concentration and the effective concentration for 50 % scavenging (EC50) was 6.1 μg/mL. The oxygen radical absorbance capacity (ORAC) for FBGI-extract was 957.7 ± 78.8 μmol of Trolox equivalent/g dry sample. Moreover, the FGBI-extract ameliorated the oxidative stress in vivo and extend the lifespan of Caenorhabditis elegans used as a model organism in this study. Consequently, D. incurvata has great potential to be considered a source of nutraceutical compounds. © 2022 Elsevier B.V.